Barack Obama Administration and the war on drugs: more continuity than change - Milani, Livia Peres [UNESP] (Inst Brasileiro Relacoes Int, 2017)
This article analyzes USA international drug policy and aims to understand if there were changes during Barack Obama administration. In order to do so, initially it presents a brief historical, then the focus is on Obama administration planning and finally it presents some observations about the police application. The partial conclusion is that there were no substantive alterations: international cooperation rests only in the security field.
Keywords: United States of America; war on drugs; Latin America